Publishing in the organizational sciences - Cummings, Larry L.; Frost, Peter J.
Summary: Publishing in the Organizational Sciences is a comprehensive overview of all aspects of the publishing process. This unique volume is written especially for the prospective author/scholar who wants to learn more about the field to advance his or her career and publishing success. Some of the topics covered in this provocative volume are the manuscript review process, publication system, newcomers' perspectives, values, reviewing manuscripts, rejection, and the editorial process. The book explains the entire context of scholarly publishing and how it should work toward advancing knowledge and successful management practice.